ANALISIS SISTEM TANGGAP DARURAT BENCANA BANJIR DI RUMAH SAKIT MARDI RAHAYU KUDUS - Kevin Reira Christian; Siswi Jayanti; Baju Widjasena (Jurnal Kesehatan Masyarakat (Undip), 2017)
Flood disaster at the beginning of 2014 yesterday in the Kudus city also affect the Mardi Rahayu Kudus Hospital. The floods can not be prevented from coming, so it requires a good emergency response system from Hospital side. This study aimed to analyze the flood disaster emergency response system at Mardi Rahayu Kudus Hospital. This research is a descriptive qualitative in-depth interviews. The informants of this study were 3 people as the main informants and one person as the informant triangulation. The results showed Mardi Rahayu Kudus Hospital already have a special policy in the face of floods. The Hospital also has procedures for evacuation when floods began to inundate several rooms in the hospital.The hospital has not been providing training and simulation of flood prevention, especially to any room personnel potentially affected by the flood disaster. Mardi Rahayu Kudus Hospital need to provide training and simulation of flood prevention, especially to any room personnel potentially affected by floods to improve the capability and responsiveness in conducting flood response, including the evacuation of patients and critical assets Hospital.